Unsur Melawan Hukum Sebagai Suatu Sarana Dalam Delik Pasal 2 Ayat (1) UU Nomor 31 Tahun 1999 Tentang Tipikor - Lubis, Muhammad Ridwan; Maryani, Halimatul; Nurita, Cut (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2019)
In all of the regulations, unless the Act No. 24 / Prp / 1960, the definition of 'unlawful' means has a broad meaning, namely in terms of formal (formele wederrechtelijkheid) and in terms of material (materiele wederrechtelijkheid), without distinguishing function is positive or negative function. This can be seen in the general explanation of these various regulations, as well as according to general explanations PTPK the existing laws in addition to an explanation related to Article 2 paragraph (1), as disampaikansebelumnya.Dalam its development in the future, the interpretation of "lawful" in the sense of material with positive function, which expanded the scope of the formulation of the offense, questioned and denied. In the Decision of the Constitutional Court (MK) No. 003 / PUU-IV / 2006 dated July 25, 2006, The Court considered that the explanation of Article 2 (1) it is contrary to the 1945 Constitution, because it creates legal uncertainty. The Court held that Article 28 D of paragraph (1) to protect the constitutional rights of citizens to obtain insurance and legal protection in criminal law certainly is translated as the principle of legality. This principle requires that the formulation of an action, so it can be regarded as a criminal offense, shall be set forth in the written rules beforehand. The Court then stated that the interpretation of the meaning of 'unlawfully' in the explanation of Article 2 (1) was not legally binding. Since then, comes back the difference of perception between the law enforcement agencies in understanding the interpretation of the element of "lawful" in the sense of material as described above, so the application of Article 2 (1) that would lead to legal uncertainty and injustice. Although this provision is widely used, the interpretation of the element of "lawful" in the practice of handling corruption cases in court Corruption (corruption) turned out to show their inconsistency.